2017
DOI: 10.1007/s00425-017-2809-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene structure, expression pattern and interaction of Nuclear Factor-Y family in castor bean (Ricinus communis)

Abstract: Nuclear Factor-Y transcription factors, which function in regulating seed development (including storage reservoir accumulation) and responding to abiotic stresses, were identified and characterized in castor bean. Nuclear Factor-Y (NF-Y) transcription factors in plants contain three subunits (NF-YA, NF-YB and NF-YC), and function as a heterodimer or heterotrimer complex in regulating plant growth, development and response to stresses. Castor bean (Ricinus communis, Euphorbiaceae) one of the most economically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…In addition, the multiple sequence alignments revealed that nearly all CsaNF-Y proteins possess evolutionarily conserved domains for DNA binding and heterotrimerization (Figure 3), which is in agreement with the NF-Y protein characteristics [14,16,41,42]. Previous studies have shown that NF-YA genes always display a highly structured intron-exon organization and the majority of them have 3-6 introns, while the NF-YB and NF-YC genes exhibit variable intron/exon organizations [15,16,41]. In this study, CsaNF-YA genes contained 2-5 introns, and multiple intron/exon organizations were observed for NF-YB and NF-YC genes (Figure 4), which is in agreement with previous studies, revealing the conserved features of the evolution of these subunits in plants.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the multiple sequence alignments revealed that nearly all CsaNF-Y proteins possess evolutionarily conserved domains for DNA binding and heterotrimerization (Figure 3), which is in agreement with the NF-Y protein characteristics [14,16,41,42]. Previous studies have shown that NF-YA genes always display a highly structured intron-exon organization and the majority of them have 3-6 introns, while the NF-YB and NF-YC genes exhibit variable intron/exon organizations [15,16,41]. In this study, CsaNF-YA genes contained 2-5 introns, and multiple intron/exon organizations were observed for NF-YB and NF-YC genes (Figure 4), which is in agreement with previous studies, revealing the conserved features of the evolution of these subunits in plants.…”
Section: Discussionsupporting
confidence: 80%
“…For example, 36 and 34 NF-Y genes were identified in Arabidopsis and rice (over 10 genes for each subunit), respectively [10,11]. In recent years, the NF-Y gene family has been identified and characterized in a number of plant species, including 23 NF-Y genes in barley (Hordeum vulgare) [12], 24 in Citrus grandis [13], 24 in peach (Prunus persica) [14], 25 in castor bean (Ricinus communis) [15], 35 in tea plant (Camellia sinensis) [16], 42 in sorghum (Sorghum bicolor) [17], 44 in banana (Musa acuminata) [18], and 51 in cassava (Manihot esculenta) [19]. Many reports have shown that NF-Y TFs are involved in various physiological and biochemical processes of plants, such as flowering [20,21], seed germination [22], hypocotyl elongation [23], photomorphogenesis [24], root development [25,26], and grain filling and endosperm development [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more plants have been discovered and studied in the NF-Y gene family, such as Brachypodium distachyon [49], Zea mays [50], Solanum lycopersicum [51], Glycine max [52], Ricinus communis [53], Poplar [54], Physcomitrella patens [55], and Vitis vinifera L. [56]. Although the NF-Y gene family has been extensively studied in the large number of plant species, there are no systematic investigations of this gene family have been reported in tea plant(Camellia sinensis L.).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results obtained from NF-Y transcription factors in A. thaliana by using BLAST (blast-2.6.0+) and HMMER, we identified 28 NF-Y genes based on the Chinese pine reference transcriptome (Table 2). Compared with the numbers of NF-Ys, such as 36 in Arabidopsis [33], 25 in castor bean [46], 59 in tomato [47], 32 in grape [48], 33 in walnut [49] and 46 in Populus trichocarpa [45] harbored a comparable number of genes. We constructed the phylogenetic tree to analyse NF-Y proteins in Chinese pine and Arabidopsis, and some studies suggest that the Arabidopsis NF-Y family may not consist of AtNF-YB11/12/13 and AtNF-YC10/11/13 because they do not include the proper structure [41].…”
Section: Discussionmentioning
confidence: 99%